Etanercept-Induced Pityriasis Lichenoides Chronica in a Patient with Rheumatoid Arthritis - Andrés F. Echeverri; Andrés Vidal; Carlos A. Cañas; Andrés Agualimpia; Gabriel J. Tobón; Fabio Bonilla-Abadía (Case Reports in Dermatological Medicine)
We present a 74-year-old female patient who developed a pityriasis lichenoides chronica (PLC) during etanercept therapy. This association is not described in the literature and might be considered in the spectrum of cutaneous adverse reactions of etanercept.